Alternative amendment for soluble phosphorus removal from poultry litter - Sarkar, Dibyendu; Salazar, Jason Mark; Punamiya, Pravin; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2010)
Background, aim, and scope: Alum (aluminum sulfate) is the currently preferred chemical amendment for phosphorus (P) treatment in poultry litter (PL). Aluminum-based drinking-water treatment residuals (Al-WTRs) are the waste by-product of the drinking-water treatment process and have been effectively used to remove P from aqueous solutions, but their effectiveness in PL water extracts has not been studied in detail. Elevated cost associated with alum could be minimized by using the equally effective WTRs to remove soluble P from PL, and they can be obtained at a minimal cost from drinking-water treatment plants. Materials and methods: We set up batch and incubation experiments to determine: (1) the effect of WTR amendment rates on PL water-extractable P (WEP) concentrations and (2) the effects of incubation time, pH, and temperature on WEP concentrations of WTR-amended PL. Results: Removal of PL-soluble P by the WTR was biphasic, showing an initial fast reaction (60% removal within 10 min) followed by a slower reaction that was completed within 12 days (90% removal). Phosphorus removal by the WTR was unaffected by pH changes in the range of 3-8. Incubation experiments showed that all WTR rates (2. 5-15 wt.%) significantly (p < 0. 001) lowered WEP concentrations in PL to ~40% of the unamended PL (no WTR) at 23°C. Discussion: Minimal reduction (20% of the unamended PL) in WEP concentrations for all WTR rates were observed up to 18 days, possibly due to P diffusion limitations. Increasing the temperature to 35°C resulted in overcoming such diffusion limitations by increasing P removal rate of reaction. Conclusions: Assuming year-round availability of adequate quantities in nearby drinking-water treatment plants, WTR may be a cost-effective treatment to reduce P availability in poultry litter. Recommendations and perspectives: Field experiments are greatly needed in order to demonstrate the excellent performance of WTR in this laboratory-based study to remove soluble P concentrations in animal waste.
Keywords: Animal waste; Drinking-water residuals; Litter; Phosphorus; Soil amendments